Criatividade e estilos parentais - Franceschini, Ana Luiza Aguiar (Universidade Federal de São Carlos, 2025)
Creativity is the ability to produce something original and appropriate to the context for which it was intended. Parenting styles are the ways in which parents deal with issues of power, hierarchy, and emotional support in relation to their children, having a significant influence on crucial areas of development. The objective of this study was to analyze whether there is a relationship between parenting styles and the creativity of individuals. The research is descriptive, inferential, with a quantitative approach. The sample consisted of 31 adult participants of both sexes who responded online to two instruments. The first consisted of two activities derived from the Thinking Creatively with Words test, which tested the participants' creative verbal fluency. The second was the Parental Authoritative Questionnaire (PAQ), which seeks to evaluate the concepts that Baumrind presents about parenting styles (permissive, authoritarian, and authoritative). The results suggest that there is no significant correlation between parenting styles and creativity. Hypotheses are made about the relationship between styles and self-efficacy. It is suggested that other measures of creativity be used, with an age limitation for participants.
Creativity and parenting styles
Keywords: Criatividade; Estilos parentais; CIENCIAS HUMANAS::PSICOLOGIA